Relation between Cardio-Ankle Vascular Index and Coronary Artery Calcification or Stenosis in Asymptomatic Subjects - Oh, Byung-Hee; Park, Jun-Bean; Park, Hyo Eun; Kim, Min Kyung; Choi, Su-Yeon (Journal of Atherosclerosis and Thrombosis, 2013)
Aim: The cardio-ankle vascular index (CAVI) is an index of arterial stiffness. We investigated the association of CAVI with the severity of coronary artery calcification (CAC) and coronary stenosis by coronary computed tomography angiography (CTA) in an asymptomatic population. Methods: A total of 549 asymptomatic Korean individuals who underwent CAVI and CTA were analyzed retrospectively. CAC and coronary stenosis were measured by CTA and assessed for the correlation with CAVI. Results: The degree of CAC and coronary stenosis demonstrated a significant correlation with CAVI (r= 0.187, p<0.001 and r= 0.212, p<0.001 for the CAC score and stenosis, respectively). After adjustment for potential confounders, including age, gender, hypertension, diabetes mellitus, and dyslipidemia, a predefined cutoff value of CAVI ≥8 was associated with advanced CAC (CAC ≥300) and significant coronary stenosis (stenosis ≥50%). Specifically, the adjusted odds ratio (95% confidence interval) of CAC ≥300 and coronary stenosis ≥50% was 3.57 (1.92-6.66) and 2.81 (1.13-7.00), respectively. Additional inclusion of CAVI improved the predictive power of the receiver operating characteristic curves for predicting coronary atherosclerosis based on traditional risk factors; the area under the curve for predicting CAC ≥300 and coronary stenosis ≥50% increased from 0.739 to 0.791 (p for difference= 0.023), and from 0.761 to 0.842 (p= 0.032), respectively. Conclusions: CAVI reflects coronary atherosclerosis and may be used as a screening tool for assessing subclinical atherosclerotic burden in an asymptomatic population.